A Loop-Mediated Isothermal Amplification Assay and Sample Preparation Procedure for Sensitive Detection of Xanthomonas fragariae in Strawberry - Wang, Hehe (PLoS One, 2016)
Xanthomonas fragariae is a bacterium that causes angular leaf spot of strawberry. Asymptomatic infection is common and contributes to the difficulties in disease management. The aim of this study was to develop a loop-mediated isothermal amplification (LAMP) assay as an efficient method for detection of asymptomatic infections of X. fragariae. In addition, a new method of sample preparation was developed that allows sampling of a larger amount of plant tissue, hence increasing the detection rate in real-life samples. The sample preparation procedure includes an overnight incubation of strawberry tissues in phosphate-buffered saline (PBS), followed by a quick sample concentration and a boiling step to extract DNA for amplification. The detection limit of the LAMP assay was approximately 2×10(3) CFU/mL for pure bacteria culture and 300 CFU/mL for bacteria spiked strawberry leaf and petiole samples. LAMP provided a 2–3 fold lower detection limit than the standard qPCR assay but was faster, and more user-friendly. The LAMP assay should serve as a rapid, sensitive and cost-effective tool for detecting asymptomatic infections of X. fragariae in strawberry nursery stock and contribute to improved disease management.